Seven NoSQL Databases in a Week : Get up and running with the fundamentals and functionalities of seven of the most popular NoSQL databases /: Get up and running with the fundamentals and functionalities of seven of the most popular NoSQL databases. (2018) - Wu, Xun (Brian); Kadambi, Sudarshan; Kandhare, Devram; Ploetz, Aaron
No abstract available